The contribution of health behaviors to socioeconomic inequalities in health: A systematic review - Petrovic, Dusan; de Mestral, Carlos; Bochud, Murielle; Bartley, Mel; Kivimäki, Mika; Vineis, Paolo; Mackenbach, Johan; Stringhini, Silvia (Preventive medicine, 2018)
Unhealthy behaviors and their social patterning have been frequently proposed as factors mediating socioeconomic differences in health. However, a clear quantification of the contribution of health behaviors to the socioeconomic gradient in health is lacking. This study systematically reviews the role of health behaviors in explaining socioeconomic inequalities in health. Published studies were identified by a systematic review of PubMed, Embase and Web-of-Science. Four health behaviors were considered: smoking, alcohol consumption, physical activity and diet. We restricted health outcomes to cardiometabolic disorders and mortality. To allow comparison between studies, the contribution of health behaviors, or the part of the socioeconomic gradient in health that is explained by health behaviors, was recalculated in all studies according to the absolute scale difference method. We identified 114 articles on socioeconomic position, health behaviors and cardiometabolic disorders or mortality from electronic databases and articles reference lists. Lower socioeconomic position was associated with an increased risk of all-cause mortality and cardiometabolic disorders, this gradient was explained by health behaviors to varying degrees (minimum contribution −43%; maximum contribution 261%). Health behaviors explained a larger proportion of the SEP-health gradient in studies conducted in North America and Northern Europe, in studies examining all-cause mortality and cardiovascular disease, among men, in younger individuals, and in longitudinal studies, when compared to other settings. Of the four behaviors examined, smoking contributed the most to social inequalities in health, with a median contribution of 19%. Health behaviors contribute to the socioeconomic gradient in cardiometabolic disease and mortality, but this contribution varies according to population and study characteristics. Nevertheless, our results should encourage the implementation of interventions targeting health behaviors, as they may reduce socioeconomic inequalities in health and increase population health. •Health behaviors are key contributors to the socioeconomic gradient in health.•Multiple health behaviors contribute more than individual health behaviors.•Smoking contributes more than alcohol, physical activity, or dietary patterns.•The contribution of health behaviors varies according to multiple factors.